Standard ECG in Brugada Syndrome as a Marker of Prognosis: From Risk Stratification to Pathophysiological Insights - Vitali, Francesco; Brieda, Alessandro; Balla, Cristina; Pavasini, Rita; Tonet, Elisabetta; Serenelli, Matteo; Ferrari, Roberto; Delise, Pietro; Rapezzi, Claudio; Bertini, Matteo (Journal of the American Heart Association, 2021)
Background The 12-lead ECG plays a key role in the diagnosis of Brugada syndrome (BrS). Since the spontaneous type 1 ECG pattern was first described, several other ECG signs have been linked to arrhythmic risk, but results are conflicting. Methods and Results We performed a systematic review to clarify the associations of these specific ECG signs with the risk of syncope, sudden death, or equivalents in patients with BrS. The literature search identified 29 eligible articles comprising overall 5731 patients. The ECG findings associated with an incremental risk of syncope, sudden death, or equivalents (hazard ratio ranging from 1.1-39) were the following: localization of type 1 Brugada pattern (in V2 and peripheral leads), first-degree atrioventricular block, atrial fibrillation, fragmented QRS, QRS duration >120 ms, R wave in lead aVR, S wave in L1 (≥40 ms, amplitude ≥0.1 mV, area ≥1 mm ), early repolarization pattern in inferolateral leads, ST-segment depression, T-wave alternans, dispersion of repolarization, and Tzou criteria. Conclusions At least 12 features of standard ECG are associated with a higher risk of sudden death in BrS. A multiparametric risk assessment approach based on ECG parameters associated with clinical and genetic findings could help improve current risk stratification scores of patients with BrS and warrants further investigation. Registration URL: https://www.crd.york.ac.uk/prospero/. Unique identifier: CRD42019123794.